2021
DOI: 10.3390/ijerph182211810
|View full text |Cite
|
Sign up to set email alerts
|

Personal Support Networks of Young People with Mild Intellectual Disabilities during the Transition to Adult Life

Abstract: Social support networks occupy a priority position requiring attention in the processes of social inclusion of people with intellectual disabilities, during their transition to adult life. The objective of the study was to analyze social support from a relational approach through Personal Network Analysis. A total of 41 young people with mild intellectual disabilities participated in the study, in two groups differentiated according to their educational stage, either compulsory secondary education or post-comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
0
2
0
1
Order By: Relevance
“…Although natural supports are essential to one's well‐being, many adults with IDD have small support networks, mainly comprised of family members (Bigby, 1997; Fullana et al, 2021; Harrison et al, 2021). In a large‐scale study examining the natural support networks of adults with IDD, Sanderson et al (2017) found that, on average, adults with IDD had two or fewer available natural supporters across life domains (ranging from an average of 1.43 supporters in employment to 2.17 supporters in recreation).…”
Section: Barriers To Natural Supportmentioning
confidence: 99%
“…Although natural supports are essential to one's well‐being, many adults with IDD have small support networks, mainly comprised of family members (Bigby, 1997; Fullana et al, 2021; Harrison et al, 2021). In a large‐scale study examining the natural support networks of adults with IDD, Sanderson et al (2017) found that, on average, adults with IDD had two or fewer available natural supporters across life domains (ranging from an average of 1.43 supporters in employment to 2.17 supporters in recreation).…”
Section: Barriers To Natural Supportmentioning
confidence: 99%
“…Although, as mentioned above, research focused on studying the personal networks of people with ID does not generally compare them with other groups, some authors have carried out such research. Fullana et al (2021) conclude, following a comparative analysis of the personal support networks of two groups of people with ID of different age ranges (27 in secondary and 14 in further education), that the change in social ties resulting from the new educational, geographical or relational contexts that occur during the transition to adulthood lead to huge changes in how support is perceived. This highlights the importance of developing socio‐educational support actions for people with ID to help them form and maintain support relationships that are high in quality and lasting sources of help.…”
Section: Introductionmentioning
confidence: 99%
“…Ahora bien, los estudios indican que las personas con discapacidad intelectual encuentran numerosas barreras para establecer y mantener las relaciones interpersonales en las distintas etapas de su vida (Sullivan, 2016;Fullana et al, 2021a). Entre estos obstáculos destaca la escasa participación social experimentada por jóvenes y personas adultas con discapacidad (Macdonald et al, 2018;Díaz-Garolera et al, 2020), situación que se detecta incluso en personas no institucionalizadas que reciben apoyos para vivir en la comunidad (van Asselt-Goverts et al, 2013;Pallisera et al, 2018).…”
Section: Introductionunclassified